Screening and identification of purine degrading Lactobacillus fermentum 9-4 from Chinese fermented rice-flour noodles - Lianghua Lu; Tiantian Liu; Xiaoling Liu; Chenghua Wang (Food Science and Human Wellness)
The aim of this study was to isolate a new purine-degrading potential probiotic strain from Chinese fermented rice-flour noodles and investigate its potential application in purine-degrading food development for promising anti-gout therapy. A new lactic acid bacteria strain designated as Lactobacillus fermentum 9-4 was screened out from 10 Shengzhamifen samples by a comprehensive method integrating agar plate selection, in vitro purine-metabolizing enzymatic activities of xanthine oxidase and urate oxidase, 16S rRNA gene sequencing and identification. The resting cells of L. fermentum 9-4 showed the maximum degradation rates of inosine and guanosine by respective 2.13 × 10−3 and 2.78 × 10−3 g/(L·min), and the highest assimilation ratio of guanosine by (55.93 ± 3.12)%, which are improvements over LAB strains characterized previously. Yogurt fermented by L. fermentum 9-4 also efficiently assimilated the inosine and guanosine, with respective degradation rates of 98.10 % and 98.56 % higher than those of the commercial ones. The L. fermentum 9-4 showed excellent survival (> 80 %) under the conditions of pH 2.5 and 0.1 % bile salt. The results suggest that L. fermentum 9-4 may be a promising candidate as a probiotic for developing low-purine foods.